Reduced Kidney Function Is Associated With Cardiometabolic Risk Factors, Prevalent and Predicted Risk of Cardiovascular Disease in Chinese Adults: Results From the REACTION Study. Issue 7 (July 2016) - Lu, Jieli; Mu, Yiming; Su, Qing; Shi, Lixin; Liu, Chao; Zhao, Jiajun; Chen, Lulu; Li, Qiang; Yang, Tao; Yan, Li; Wan, Qin; Wu, Shengli; et al.
Abstract : Background: Chronic kidney disease (CKD) increases cardiovascular disease (CVD) risk. However, the association of mildly reduced kidney function with CVD risk is unclear. Methods and Results: This study investigated the association of estimated glomerular filtration rate (eGFR) with prevalent CVDs, 10‐year Framingham risk for coronary heart disease (CHD), and 10‐year risk of atherosclerotic cardiovascular diseases (ASCVD) in 239 832 participants from the baseline of the Risk Evaluation of cAncers in Chinese diabeTic Individuals: a lONgitudinal study. With an interviewer‐assisted questionnaire, we collected information on CVD, including reported CHD, stroke, or myocardial infarction. Chronic Kidney Disease–Epidemiology Collaboration (CKD‐EPI) equation was used to calculate eGFR. Compared with individuals with normal eGFR (≥90 mL/min per 1.73 m 2 ), those with decreased eGFR (75–89, 60–74, and <60 mL/min per 1.73 m 2 ) had higher risk of prevalent obesity, diabetes mellitus, hypertension, and dyslipidemia in both men and women ( P for trend all <0.001). Moreover, a significantly higher 10‐year Framingham risk for CHD and 10‐year risk for ASCVD was observed in both men and women with mildly decreased eGFR (60–89 mL/min per 1.73 m 2 ). Conclusions: Even mildly reduced eGFR (under 90 mL/min per 1.73 m 2 ) is associated with elevated 10‐year Framingham risk for CHD and 10‐year ASCVD risk among Chinese adults.